Finite Element Analysis of Rigid Pavement Over Improved Subgrade Using Nanomaterial in Karawang Regency, Indonesia - Mulyadi Yuswandono; Andri Krisnandi Somantri; Atmy Verani Rouly Sihombing; Aditia Febriansya; Daniel Octova Agusaputra; Salma Fadhilah Suryadi (Department of Civil Engineering, Politeknik Negeri Bandung, 2022)
In this paper, the influence of improved subgrade condition of rigid pavements using nanomaterials using Finite Element Method will be discussed. The soil used as subgrade is obtained from National North Coast Road Corridor in Karawang Regency, Indonesia and categorized as soft clay or CH. Soft soil is a type of soil with low bearing capacity and high compressibility. This causes problems on rigid pavements; one example is cracks due to settlements of subgrade. Soft subgrade needs to be improved so that the rigid pavement will not deteriorate during design life. This study aims to analyze the displacement of rigid pavement over subgrade layer before and after soil improvement with the addition of 4% Nano Lime and 4% Nano Silica. The rigid pavement analysis was modeled in the form of a slab with a size of 4 x 6 meters and uses different thickness variations, namely 15, 20, 25, and 30 cm with concrete quality 20 MPa and 30 MPa. The vehicle load is modeled as a static concentrated load or assumed to be at rest, parked, and the speed is below 5 km/hour. The result of the analysis shows the largest total displacement of rigid pavement occurs before soil